Guide du chercheur américaniste à Rio de Janeiro - Sílvia Capanema P. de Almeida (Centre de Recherches sur les Mondes Américains, 2012)
This research guide presents an overview of the main documentation centers and public archives of the city of Rio de Janeiro. For each institution, it describes the contents (sources, archivist funds, collections, etc.) as well as the practical aspects (access, on-site contacts, electronic resources, etc.). In order to facilitate the work of students and academics, the guide also includes information about everyday life in Rio de Janeiro.